Development and evaluation of bio-formulation for growth and suppression of white root rot disease in rubber seedlings - Imran, Shabbir (2020)
White root rot (WRR) disease caused by Rigidoporus microporus is a serious problem of rubber trees. Fungicides are used to control WRR disease, but they cause fungicide resistance. Moreover, fungicides effectiveness depends on early detection of disease, while use of biocontrol agents would be an effective approach to control WRR disease. Silicon (Si) is a beneficial element that increases disease resistance, but it is mostly present in insoluble forms. Silicate solubilizing bacteria (SSB) are biocontrol agents that can solubilize insoluble silicates. Arbuscular mycorrhizal fungi (AMF) are known to improve nutritional status of plants. This study evaluated SSB isolate from rubber rhizosphere and AMF (Glomus mosseae) with Si for growth promotion and WRR disease suppression in rubber seedlings, and then evaluated the efficacy of peat based bio-formulation of SSB and AMF with Si for WRR disease suppression. A laboratory study was conducted to isolate and characterize SSB isolates and then screened for growth promotion of rubber seedlings in a glasshouse study. Two glasshouse studies were conducted using selected UPMSSB7 isolate from isolation study and AMF with Si for growth promotion and WRR disease suppression. The peat based bioformulation of UPMSSB7 and AMF with Si was developed to evaluate its shelf life during 24 weeks of storage. A glasshouse study was conducted to evaluate bioformulation of UPMSSB7, AMF with Si for WRR disease suppression compared with fungicide. The results from in vitro study revealed that UPMSSB7 (Enterobacter sp.) had the highest solubilization of silicate (11.55 mg L-1) in liquid assay at 10 DAI and inhibition of R. microporus (57.24%). The glasshouse study revealed that UPMSSB7 with Si had the highest growth parameters of rubber seedlings. Thus, UPMSSB7 was selected for subsequent studies. The growth promotion study revealed that coinoculation (T5) had the highest stem height (104.8 cm), leaf area (3510.7 cm2), shoot and root dry weight (29.22 g and 29.20 g, respectively). The WRR disease suppression study revealed that co-inoculation (T5) had the lowest disease incidence (DI, 16%), disease severity of foliar (DSF, 14%) and root rot symptoms (DRS, 12%). The bioformulation study revealed that bio-formulation of UPMSSB7 and AMF with Si (T4) had the highest shelf life of bio-formulation during 24 weeks of storage. The glasshouse study revealed that bio-formulation of UPMSSB7 and AMF with Si (T4) reduced WRR disease as effectively as fungicide and had the lowest DI, DSF and DSR (18%, 17% and 16%, respectively). It was concluded that bio-formulation could be used as an effective sustainable approach to suppress WRR disease in rubber seedlings at nursery stage to reduce the use of fungicides.